Varied Mechanisms of Gas Exchange Parameters in Response to Altered Moisture Levels in Drought-Tolerant Cluster Bean [Cyamopsis Tetragonolaba (L.) Taub.] Genotypes - Seenaiah, Ragula; Babu , Kakumanu; Naik, Banavath Jayanna; Basha, Pinjari Akbar; Shanthi, Penumalli; Naik, Subba Naik Gari Thimma (International Journal of Membrane Science and Technology, 2023)
An effort was made at Regional Agricultural Research Station (RARS), Rekulakunta to study the physiological attitudes of cluster bean (Cyamopsis tetragonoloba) against different water regimes such as 100%, 80%, 60%, 40%. Six cluster bean genotypes were grown in pots in a complete random block design (CRBD) and were regularly irrigated. Plants were subjected to drought treatment at 39 days after sowing (DAS) for 8 days. On the 46th day of sowing photosynthetic rate (PN), stomatal conductance (gS), transpiration (E), internal CO2 (Ci) were measured. Intrinsic water use efficiency (WUEi), relative water content (RWC), SPAD chlorophyll meter reading (SCMR) and specific leaf area (SLA) were determined using standard protocols. The maximum PN, gS, E, and Ci were recorded at 60% water level coupled with RWC, SCMR, and SLA. With the increased drought, genotypes showed reduced PN, gS, E, and Ci except in varieties RGC-1025 and RGC-936. WUEi showed a negative correlation with PN, gS, E, and Ci indicating the genotypical efficiency in copping water stress.